Dramatic closure reading the end - Schlueter, June 1942- (Fairleigh Dickinson Univ. Press [u.a.], 1995)
In her theoretical discussion, Schlueter explores how literary, theatrical, and cultural conventions cooperate and collide; how the dramatic or performance text designates what Wolfgang Iser calls a text's "response-inviting structure"; how that structure activates conventions and predispositions throughout its sequence of reading moments, shaping, frustrating, and satisfying expectations; and how readers constitute texts as they read toward closure. The assumption throughout is that all texts, whether stable or transgressive, necessarily engage the question of how, when, and where to end and that all readers, whether of literary or performance texts, are implicated in closure